用于输送液体添加剂的装置 (2018)
本发明涉及种用于输送液体添加剂(38)的装置(1)，该装置具有：用于储存液体添加剂(38)的储箱(2)；抽吸点(3)，液体添加剂(38)可通过装置(1)的泵(4)在该点被吸出储箱(2)；覆盖所述抽吸点(3)的过滤器(5)，所述过滤器至少部分地界定位于过滤器(5)与抽吸点(3)之间的中间空间(6)，并使中间空间(6)与储箱(2)的内部空间(7)分开，其中，所述过滤器(5)包括具有顶边(9)和底边(10)的过滤器表面(8)，其中，顶边(9)和底边(10)在垂直方向(11)上彼此间隔开30mm[毫米]至80mm并且抽吸点(3)在垂直方向(11)上定位在顶边(9)下方最多5mm处。 A device for delivering a liquid additive includes: a tank configured to store the liquid additive; a pump; a suction point at which the liquid additive can be sucked out of the tank by the pump; and a filter at least partially delimiting an intermediate space between the filter and the suction point and separating the intermediate space from an interior space of the tank. The filter has a filter surface with a top edge and a bottom edge, the top edge and the bottom edge being spaced apart from one another in a vertical direction by 30 mm to 80 mm and the suction point being positioned at most 5 mm below the top edge in the vertical direction.